2021
DOI: 10.1080/0284186x.2021.1958005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and factors associated with COVID-19-related death and morbidity among hospitalized patients with cancer: a Swedish cohort study

Abstract: Introduction: Cancer patients are considered to have a higher risk of dying and developing severe Coronavirus Disease 2019 (COVID-19). To date, there are few studies including co-morbidities and sociodemographic factors when investigating the outcome of COVID-19 in a cohort of cancer patients. In this study, we analyzed cancer patients that have been hospitalized due to COVID-19 during the first wave of the pandemic in Sweden to investigate the impact of COVID-19 on mortality and morbidity. Patients and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Older age leads to a deficiency in the immune response, resulting in a higher risk of death in COVID-19 patients [ 41 ]. The strength and direction of the association between age and COVID-19 mortality have been consistently found across multiple studies [ 10 12 , 27 , 29 32 , 38 40 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Older age leads to a deficiency in the immune response, resulting in a higher risk of death in COVID-19 patients [ 41 ]. The strength and direction of the association between age and COVID-19 mortality have been consistently found across multiple studies [ 10 12 , 27 , 29 32 , 38 40 ].…”
Section: Discussionmentioning
confidence: 81%
“…In our study, we observed this association, although it was not significant. Findings in this regard are contradictory; some studies have found it to be a risk factor for death in COVID-19 [ 10 , 11 , 27 , 32 ], while others have not [ 12 , 38 40 ]. In contrast, the non-association between the type of cancer, solid tumor or hematological neoplasm, and the probability of death in COVID-19 patients coincides with several studies [ 10 12 , 27 , 30 32 , 39 ].…”
Section: Discussionmentioning
confidence: 99%